An assessment of central-peripheral ventilatory chemoreflex interaction using acid and bicarbonate infusions in humans. - Clement, I; Pandit, J; Bascom, D; Dorrington, K; O'Connor, D; Robbins, P (1995)
1. The object of this study was to investigate the effect of central chemoreceptor stimulation on the ventilatory responses to peripheral chemoreceptor stimulation. 2. The level of central chemoreceptor stimulation was varied by performing experiments at two different levels of end-tidal CO2 pressure (PCO2). Variations in peripheral chemoreceptor stimulus were achieved by varying arterial pH (at constant end-tidal PCO2) and by varying end-tidal O2 pressure (PO2). 3. Two protocols were each performed on six human subjects. In one protocol ventilatory measurements were made during eucapnia, when the arterial pH was lowered from 7.4 to 7.3. The variation in pH was achieved by the progressive infusion of acid (0.1 M HCl). In the other protocol ventilatory measurements were made during hypercapnia, when the arterial pH was increased from 7.3 to 7.4. The variation in pH was achieved by the progressive infusion of 1.26% NaHCO3. In each protocol ventilatory responses were measured during euoxia (end-tidal PO2, 100 Torr), hypoxia (end-tidal PO2, 50 Torr) and hyperoxia (end-tidal PO2, 300 Torr), with end-tidal PCO2 held constant. 4. The increase in ventilatory sensitivity to arterial pH induced by hypoxia (50 Torr) was not significantly different between protocols (acid protocol, -104 +/- 31 l min-1 (pH unit)-1 vs. bicarbonate protocol, -60 +/- 44 l min-1 (pH unit)-1; mean +/- S.E.M.; not significant (n.s.)). The ventilatory sensitivity to hypoxia at an arterial pH of 7.35 was not significantly different between protocols (acid protocol, 14.7 +/- 3.3 l min-1 vs. bicarbonate protocol, 15.6 +/- 2.4 l min-1; mean +/- S.E.M.; n.s.). The results provide no evidence to suggest that peripheral chemoreflex ventilatory responses are modulated by central chemoreceptor stimulation.